Diagnosis and treatment of cyclic corpus luteum and trophic inactive ovary in cattle - ARYAN, Hussam; BOGDAN, Liviu; MARDENLI, Omar; GROZA, Ioan (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The objectives of this study evaluating induction of ovulation, of a total number of 75 cows in the farm were examined transrectal (manual) supported by ultrasonographic examination, a number of 13 cows (17.33%) were diagnosed suffering reproduction disorder (trophic inactive ovaries and cyclic and persistent corpus luteum), all 6 cows (8%) from the total number of cows in the farm were suffering trophic inactive ovaries and treated with (Serigon product) i.m, 3 cows (50%) remained pregnant after treatment, the conception rates after first and second insemination were 33.33%, 50% and 16.66% respectively (P < 0.05). 7 cows (9.33%) diagnosed with cyclic and persistent corpus luteum and treated with Prostaglandin F2α (Dinolytic product) i.m, a number of 6 cows (85.72%) (P < 0.05) remained pregnant after treatment